2002
DOI: 10.1248/cpb.50.788
|View full text |Cite
|
Sign up to set email alerts
|

Structural Requirements of Flavonoids and Related Compounds for Aldose Reductase Inhibitory Activity.

Abstract: The methanolic extracts of several natural medicines and medicinal foodstuffs were found to show an inhibitory effect on rat lens aldose reductase. In most cases, flavonoids were isolated as the active constituents by bioassay-guided separation, and among them, quercitrin (IC 50 ‫51.0؍‬ m mM), guaijaverin (0.18 m mM), and desmanthin-1 (0.082 m mM) exhibited potent inhibitory activity. Desmanthin-1 showed the most potent activity, which was equivalent to that of a commercial synthetic aldose reductase inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
156
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(165 citation statements)
references
References 46 publications
8
156
0
1
Order By: Relevance
“…The results suggest that two simple phenolic compounds (5, 6) having 2,5-dihydroxy benzene moieties exhibit somewhat lower potencies than that carrying a catechol moiety as suggested in flavonoids and related compounds for AR inhibitory activity. 19) We concluded that the observed activity in the crude EtOAc extract (IC 50 ϭ0.8 mg/ml) was probably attributable to the contribution of the inhibitory effects of unknown polyphenols or other compounds present and/or the synergistic effect of individual AR inhibitory constituents when tested in the form of a complex mixture. It has been acknowledged that plant-derived extracts and phytochemicals are potential alternatives to synthetic inhibitors against AR.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The results suggest that two simple phenolic compounds (5, 6) having 2,5-dihydroxy benzene moieties exhibit somewhat lower potencies than that carrying a catechol moiety as suggested in flavonoids and related compounds for AR inhibitory activity. 19) We concluded that the observed activity in the crude EtOAc extract (IC 50 ϭ0.8 mg/ml) was probably attributable to the contribution of the inhibitory effects of unknown polyphenols or other compounds present and/or the synergistic effect of individual AR inhibitory constituents when tested in the form of a complex mixture. It has been acknowledged that plant-derived extracts and phytochemicals are potential alternatives to synthetic inhibitors against AR.…”
Section: Resultsmentioning
confidence: 88%
“…It has been acknowledged that plant-derived extracts and phytochemicals are potential alternatives to synthetic inhibitors against AR. 19,23,27) Currently, the compounds isolated from plants as AR inhibitors are classified as flavonoids, [19][20][21][22][23][24][25][26] stilbenes, 19) terpenoids, 21) ellagic acid and its derivatives, 28) and alkaloids. The present study was carried out in a search for new potential AR inhibitors from the fruiting bodies of G. applanatum, and cerebrosides (3), 2,5-dihydroxybenzoic acid (6) and protocatechualdehyde (7) were isolated as active principles which may be useful for the treatment of diabetic complications.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the chalcone backbone could be a versatile scaffold for drug design. A survey of the literature revealed that some natural [9,10] and synthetic chalcones [11] showed significant ALR2 inhibitory activities, and this prompted us to investigate potential ARIs derived from chalcone-based compounds. Thus, we focused on the compounds having a carboxylic acid moiety that was incorporated into the chalcone backbone and synthesized these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Anthocyanin is one type of polyphenols that can prevent glycotoxin formation. A study explains that phenolic antioxidants, in addition as a free radical scavenger, are serving as an AGE inhibitor [14]. Anthocyanin can inhibit the formation glycotoxin through inhibition of auto-oxidation monosaccaride [15].…”
mentioning
confidence: 99%